Electronic and ligating properties of carbocyclic carbenes: A theoretical investigation. Issue 5 (14th December 2018) - Bhagat, Shweta; Arfeen, Minhajul; Das, Gourav; Patel, Neha; Bharatam, Prasad V.
Abstract : Carbocyclic carbenes (CCCs) are a class of nucleophilic carbenes which are very similar to N ‐heterocyclic carbenes (NHCs) in terms of their reactivity, but they do not contain a stabilizing heteroatom in their cyclic ring system. In this study, 17 representative known CCCs and 34 newly designed CCCs are evaluated using quantum chemical methods, and the results are compared in terms of their stability, nucleophilicity, and proton affinity (PA) parameters. The results are divided on the basis of ring size of the known and reported CCCs. The stability, nucleophilicity, PA, complexation energy, and bond strength–related parameters were estimated using M06/6‐311++G(d, p) method. The results indicated that the CCCs known in the literature are strong σ‐electron donating species and have considerable π‐accepting properties. This study led to the design and identification of a few new CCCs with dimethylamine and diaminomethynyl substituents which can be singlet stable and are substantially nucleophilic. © 2018 Wiley Periodicals, Inc. Abstract : Carbocyclic carbenes are interesting species but still lack thorough investigation based on their stability and reactivity. This is a systematic effort to understand different properties of CCCs with variable ring sizes. This work also exploits some promising substitutions to establish a balance between the nucleophilic properties and stability.